PENGARUH KARAKTERISTIK INDIVIDU, KOMITMEN ORGANISASI, DAN DUKUNGAN ORGANISASI TERHADAP KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN GIANYAR - Ni Kadek Sinta Jayanti; I Nengah Suardhika; Ni Putu Cempaka Dharmadewi Atmaja (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
This research aims to determine the effect of individual characteristics, organizational commitment, and organizational support partially and simultaneously on employee performance at Badan Kepegawaian dan Pengembangan Sumber Daya Manusia, Kabupaten Gianyar. The population and sample in this research were ASN employees at the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia, Kabupaten Gianyar, totaling 40 people. Where the sample selection method used in this research is the census method. Data collection was carried out through interviews and questionnaires with the analysis technique used was Multiple Linear Regression Analysis. The results of the research show that partially and simultaneously individual characteristics, organizational commitment, and organizational support have a positive and significant effect on employee performance at the Gianyar Regency Personnel and Human Resources Development Agency. Where from the tests carried out it can be seen that the organizational support variable has a more dominant influence than organizational commitment and organizational support.